Integrating Artificial Intelligence in Vocational Higher Education: A Case Study at Politeknik Penerbangan Makassar - Agung Raharjo, M.; Rossydi, Ahmad; Burhanuddin, Fachrurrazy; Octavianie, Adhitya; Idyaningsih, Nining; Sukarman, Sukarman (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
This study seeks to gauge the implementation, effectiveness, and lecturers’ perceptions of artificial intelligence (AI) integration in teaching at Politeknik Penerbangan Makassar, Indonesia. A mixed-methods approach was employed, utilizing Likert-scale questionnaires to measure implementation and effectiveness, and open-ended questionnaires to assess lecturers’ perceptions. The quantitative findings indicate that AI implementation is generally effective (mean = 4.00), with institutional policies and opportunities for student innovation being key factors, while infrastructure presents an obstacle. Qualitative results indicate that lecturers view AI as a transformative tool for enhancing teaching efficiency, providing instant and consistent feedback, and fostering creativity and collaboration. However, despite its benefits, lecturers emphasize the essential nature of human guidance, such as contextual feedback, emotional support, or ethical oversight. The novelty of the study’s approach lies in its focus on vocational higher education, a subject that has relatively little empirical evidence, and demonstrates how the introduction of AI can supplement rather than replace pedagogues’ work in learning. The implications of the findings provide practical guidance for policymakers and educators seeking more comprehensive institutional policies, targeted faculty development, and investment in technological infrastructure to leverage AI in teaching and learning effectively.